Pengaruh Etnosentrisme, Sikap, Norma Subjektif, dan Kontrol Perilaku terhadap Niat Beli Sepatu Lokal Ventela - Fikri Farhan; Aditya Yudha Kusuma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The dominance of foreign footwear brands in Indonesia remains strong despite the growing awareness of supporting local products. This phenomenon raises questions about the factors that drive consumer purchase intention toward local brands, particularly among younger generations. This study aims to examine the influence of ethnocentrism, attitude, subjective norms, and perceived behavioral control on the purchase intention of Ventela, a local footwear brand, using the Theory of Planned Behavior (TPB) framework. A quantitative approach was employed by distributing questionnaires to 150 respondents in Yogyakarta who had never purchased or used Ventela products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that ethnocentrism, attitude, subjective norms, and perceived behavioral control significantly and positively affect consumers’ purchase intention toward Ventela. Theoretically, this study extends the application of TPB by incorporating ethnocentrism as an additional predictor of purchase intention for local products. Practically, the findings suggest that producers should emphasize national pride in their marketing strategies, enhance product quality and design, and expand purchasing accessibility. The main limitation of this study lies in its focus on a single brand and a limited sample size, suggesting that future research should broaden the context and include more diverse respondents.